What are the determinants for individuals to undergo cardiovascular disease health checks? A cross sectional survey - Cheong, Ai Theng; Khoo, Ee Ming; Liew, Su May; Chinna, Karuthan (Public Library of Science, 2018)
Background There is a need to improve public’s participation in health checks for early identification of individuals at high risk of CVD for prevention. The objective of this study is to identify significant determinants associated with individuals’ intention to undergo CVD health checks. These determinants could be used to develop effective strategies to improve CVD health check participation. Methods This was a cross sectional survey using mall intercept interviews. It was carried out in a hypermarket surrounded by housing estates with a population of varying socioeconomic backgrounds. Inclusion criteria were Malaysian nationality and age 30 years and older. The validated CVD health check questionnaire was used to assess participants’ intention and the determinants that influenced their intention to undergo CVD health checks. Results A total of 413 participants were recruited. The median age of the participants was 45 years (IQR 17 years) and 60% of them were female. Participants indicated they were likely (45.0%) or very likely (38.7%) to undergo CVD health checks while 16.2% were not sure, unlikely or very unlikely to undergo health checks. Using ordinal regression analysis, perception of benefits, drawbacks of CVD health checks, perception of external barriers and readiness to handle outcomes following CVD health checks were the significant determinants of individuals’ intention to undergo CVD health checks. Conclusions To improve individuals’ participation in CVD health checks, we need to develop strategies to address their perception of benefits and drawbacks of CVD health checks, the perceived external barriers and their readiness to handle outcomes following CVD health checks.